PERAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) KOTA PEKANBARU DALAM PENGELOLAAN SUMBER DAYA AIR TAHUN 2016 - Setiawan, M. Iqbal; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Management of water resources is a process that encourages integration between development and management of water, land, and other resources, with the aim of maximizing socio-economic welfare and paying attention to the sustainability of the ecosystem. Besides that, water resources management is a method for formulating patterns and plans for managing water resources, and is not an end goal. In its implementation, several laws and regulations and policies have been refined, including the enactment of Law Number 7 of 2004 concerning Water Resources (SDA Law) which has included the principles and Presidential Regulation (Perpres No. 12 of 2008) concerning Management Water Resources and National Policies on Management of Water Resources.This law aims to implement water management in a comprehensive, sustainable manner, and through an open approach so as to provide an option for business communities and non-governmental organizations to participate in the planning and implementation of integrated water resources management processes. The purpose of this study was to find out the Role of Public Works and Spatial Planning (PUPR) in the management of Water Resources in Pekanbaru City in 2016.The conclusion of this study shows that the Department of Public Works and Spatial Planning (PUPR) in the City of Pekanbaru in the Management of Water Resources in Pekanbaru in 2016 has not been optimal, even in 2016 it was only a normal operation, while the construction of water infrastructure was not due to budget factors, lack of human resources, inadequate heavy equipment due to the age factor of the device. Keywords: the role of public works and Spatial Planning (PUPR), water resources management.